Lietuvos Respublikos Konstitucinio Teismo jurisprudencijos įtaka žaliosios ekonomikos įgyvendinimui Lietuvoje - Juškevičiūtė-Vilienė, Agnė (Vilnius University Open Series, 2024)
The objective of this interdisciplinary legal and economic article is to examine how the jurisprudence of the Constitutional Court of the Republic of Lithuania, which has evolved over three decades, impacts the implementation of the green economy in Lithuania. To accomplish this aim, the article first explains the concept of the green economy in line with the economic and legal doctrine. The article analyses the constitutional bases of freedom of individual economic activity and environmental protection established in the Constitution of the Republic of Lithuania. It then explores how the Constitutional Court aims to reconcile environmental demands and freedom of individual economic activity, and how this case law supports the deployment of the green economy.